Team sport athletes may be less likely to suffer anxiety or depression than individual sport athletes - Pluhar, E.; McCracken, C.; Griffith, K. L.; Christino, M. A.; Sugimoto, D.; Meehan III, W. P. (Journal of Sports Science & Medicine, 2019)
The objective of the study was to determine whether 1) the proportion of athletes with mental health diagnoses and 2) athlete motivations for playing differ between team sports and individual sports. We conducted a cross-sectional study of child and adolescent athletes assessed at a sports injury prevention center. We compared self-reported anxiety, depression, and reasons for participating in sports between athletes in individual sports (e.g. gymnastics, running, diving) and team sports (e.g. soccer, football, hockey). In addition, we categorized motivation for participating in sports as 1) for fun, with associated benefits of participation including, motives such as making friends and being part of a team or 2) for goal-oriented reasons with associated benefits of participation including motives such as obtaining scholarship or controlling weight. At the time of this analysis, 756 athletes between the ages of 6 and 18 years had undergone a sports injury prevention evaluation. Most athletes were White (85%) and there was a slight female predominance (56%). Of the total population, 8% reported suffering from anxiety or depression. A higher proportion of individual sport athletes reported anxiety or depression than team sport athletes (13% vs. 7%, p < 0.01). Individual sport athletes were more likely than athletes in team sports to play their sports for goal-ori ented reasons, as opposed to for fun (30% vs. 21%, p < 0.05). Individual sport athletes are more likely to report anxiety and depression than team sport athletes. The mental health benefits of participation in organized sports may vary between individual sport athletes and those playing team sports.